2015
DOI: 10.1002/hed.24041
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of bevacizumab + cetuximab + cisplatin with concurrent intensity‐modulated radiation therapy for patients with stage III/IVB head and neck squamous cell carcinoma

Abstract: Background To evaluate the efficacy and tolerability of the addition of two monoclonal antibodies, bevacizumab and cetuximab, to two cycles of high-dose cisplatin administered concurrently with IMRT for HNSCC. Methods Patients with newly diagnosed stage III/IVB (M0) HNSCC received cetuximab (400 mg/m2 loading dose, followed by 250 mg/m2 weekly), bevacizumab (15 mg/kg, days 1 and 22), and cisplatin (50 mg/m2, days 1, 2, 22, and 23) concurrently with IMRT (70 Gy). The primary endpoint was progression free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…In accordance with previous studies (5), an earlier epidemiological analysis for patients with oral cancers in China has shown that over a half of the examined oral malignancies are SCC (6), suggesting SCC as the predominate oral malignancy. Despite recent advances in novel therapies (7), the prognosis for patients with OSCC remains poor (8). Thus, it is imperative to identify a novel therapeutic target in OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous studies (5), an earlier epidemiological analysis for patients with oral cancers in China has shown that over a half of the examined oral malignancies are SCC (6), suggesting SCC as the predominate oral malignancy. Despite recent advances in novel therapies (7), the prognosis for patients with OSCC remains poor (8). Thus, it is imperative to identify a novel therapeutic target in OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, a phase II study of the addition of Bevacizumab to Cisplatin plus intensity modulated radiation therapy (IMRT) did not show any significant increase in toxicity, with a 2 year PFS rate of 76% and overall survival rate of 88% 54 . With the addition of Cetuximab to the above regimen, the same authors showed an improved progression free survival to 89% and overall survival to 93% 55 . Cetuximab and bevacizumab have also been evaluated together in recurrent or metastatic HNSCC and showed tumor growth inhibition both in vitro and in vivo , and in the clinical trial showed a disease control rate of 73% and OS of 7.5 months 56 .…”
Section: Monoclonal Antibody Therapiesmentioning
confidence: 90%
“…Several clinical studies have yielded positive results when using a combination of bevacizumab, cetuximab, and chemotherapy in addition to radiation or when adding bevacizumab to the combination of erlotinib, chemotherapy, and radiation [17][18][19]. Further exploration of these combined strategies and their safety profiles thus seems like a promising direction to pursue.…”
Section: Promising Trials and Next Steps To Overcome Resistancementioning
confidence: 99%